Framing Effects in Development Assistance Perceptions: A Cross-Country Comparison between Indonesia and Malaysia - Akhyar, M.; Rahmi, R. (Manunggal Halim Jaya, 2025)
This study examines the influence of framing effects on public perceptions of development assistance through a qualitative literature-based approach, focusing on a cross-country comparison between Indonesia and Malaysia. The research aims to explore how different framing strategies—such as loss versus gain, ownership versus charity, and donor identity—shape perceptions of necessity, fairness, legitimacy, and alignment with national interests in two socio-politically distinct but culturally proximate contexts. Methodologically, the study synthesizes theoretical and empirical findings from political communication, development studies, and Southeast Asian media scholarship. Literature was systematically collected from peer-reviewed journals, policy reports, and relevant grey literature, then thematically coded to identify recurrent patterns, contextual moderators, and institutional influences. The results indicate that loss-framed messages generally heighten perceived urgency, while ownership and partnership frames are more effective in sustaining legitimacy, particularly when supported by transparency and participatory practices. Donor identity framing significantly affects legitimacy perceptions, with narratives emphasizing mutual benefit and co-prosperity outperforming those suggesting strategic competition or dependency. Country-specific differences emerge: Indonesian audiences respond more positively to frames highlighting transparency and community ownership, whereas Malaysian audiences are more receptive to frames underscoring competence, stability, and alignment with national development plans. The findings contribute theoretically by integrating cognitive and sociological framing theories with institutional and cultural moderators, and managerially by offering context-sensitive communication strategies for policymakers, donors, and civil society actors. This research underscores the necessity of aligning message content, messenger credibility, and institutional practice to maximize the positive impact of development assistance narratives.